Potential Association Between Dietary Fibre and Humoral Response to the Seasonal Influenza Vaccine - Cait, Alissa; Mooney, Anna; Poyntz, Hazel; Shortt, Nick; Jones, Angela; Gestin, Aurélie; Gell, Katie; Grooby, Alix; O’Sullivan, David; Tang, Jeffry S.; Young, Wayne; Thayabaran, Darmiga; et al. (Frontiers in Immunology, 2021)
Influenza vaccination is an effective public health measure to reduce the risk of influenza illness, particularly when the vaccine is well matched to circulating strains. Notwithstanding, the efficacy of influenza vaccination varies greatly among vaccinees due to largely unknown immunological determinants, thereby dampening population-wide protection. Here, we report that dietary fibre may play a significant role in humoral vaccine responses. We found dietary fibre intake and the abundance of fibre-fermenting intestinal bacteria to be positively associated with humoral influenza vaccine-specific immune responses in human vaccinees. Importantly, this association was largely driven by first-time vaccinees; prior influenza vaccination negatively correlated with vaccine efficacy. Similarly, dietary fibre consumption enhanced humoral influenza vaccine responses in mice, where the effect was mechanistically linked to short-chain fatty acids, the bacterial fermentation product of dietary fibre. Overall, these findings may bear significant importance for emerging infectious agents, such as COVID-19, and associated de novo vaccinations.